2020
DOI: 10.3390/ma13163544
|View full text |Cite
|
Sign up to set email alerts
|

Is Biochar from the Torrefaction of Sewage Sludge Hazardous Waste?

Abstract: Improved technologies are needed for sustainable management of sewage sludge (SS). The torrefaction (also known as biomass “roasting”) is considered a pretreatment of SS before use in agriculture. However, it is not known whether the torrefaction has the potential to decrease heavy metals’ (HMs) leachability and the SS toxicity. Thus, the aim of the study was to evaluate the influences of the SS torrefaction parameters (temperature and process time) on HM contents in biochar, HM leachability, and biochar toxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…Freshly produced PAHs-contaminated biochar released PAHs in soils and the level of PAHs released decreased with aging ( Sigmund et al., 2017 ). The pattern of PTEs leaching observed in sewage sludge biochar is similar to what is obtainable with the non-pyrolyzed biosolids ( Bialowiec et al., 2020 ). This implies that conversion of biosolids to biochar has no significant impact on the reduction of PTEs.…”
Section: Challenges and Limitations Of Biochar Applicationsupporting
confidence: 69%
“…Freshly produced PAHs-contaminated biochar released PAHs in soils and the level of PAHs released decreased with aging ( Sigmund et al., 2017 ). The pattern of PTEs leaching observed in sewage sludge biochar is similar to what is obtainable with the non-pyrolyzed biosolids ( Bialowiec et al., 2020 ). This implies that conversion of biosolids to biochar has no significant impact on the reduction of PTEs.…”
Section: Challenges and Limitations Of Biochar Applicationsupporting
confidence: 69%
“…Moreover, Białowiec et al (2020) [ 135 ] conducted research on toxicity of the bio-char from torrefaction of SS, the results showed that increasing temperature and resident time leads to the toxicity reduction. However, toxic HMs was independent on time and temperature.…”
Section: Municipal Sewage Sludge Treatment and The Resource Recoverymentioning
confidence: 99%
“… Generation of leachate, waste of valuable organic/inorganic materials, emission of greenhouse gases if not engineered Cheap process with no energy consumption, reduces SS volume [ 85 , 87 ] Farm land Direct use of SS without any treatment Contamination of heavy metals Great source of inorganic/organic substances as fertilizer or to improve soil properties [ 81 , 149 ] Drying 60–93 °C. Spread of waste/SS on open bed of sand and allowed to remain until dry Climate dependent, unstable temperature conditions, cover large land surface, emit odor, heavy metals pollution Performed in natural way, affordable, destroy pathogen, reduce sludge volume [ 136 , 138 ] Dewatering 30–70 °C and 1–300 bar Minimization of water content from SS for its effective disposal This treatment process can't mitigate HMs pollution in SS Improve bio-energy utilization, reduce volume, easy transportation, lessen leachate in landfills, does not contribute to carbon emission [ 61 ] Torrefaction >300 °C Low/slow thermal process in oxygen starving environment Pollution of HMs through different application of torrefied product Produce high amount of biochar, improves solid fuel properties, low energy consumption, short torrefaction time, enhance carbon fixation and hydrophobicity of torrefied material [ 134 , 135 ] Incineration Temperatures of 750–925 °C (1400–1700 °F). Residence times are typically 2–5 s. Straight combustion in excess oxygen supply Expensive, emit some pollutant gases such us furans and nitrous, ammonia emission, leads to the second pollution via residue (ash) Odor minimization, reduction of raw waste mass (SS), production of energy.…”
Section: Municipal Sewage Sludge Treatment and The Resource Recoverymentioning
confidence: 99%
“…Even though forests cover approximately 58% of the country's area, municipal solid waste, industrial waste, or sewage sludge could replace lignocellulosic biomass in thermochemical processes [30,31] due to environmental friendliness and costeffectiveness [32,33]. Sewage sludge (SS) co-combustion has been studied recently for energy utilization while improving organic compounds share [34,35]. Sewage sludge is an incidental product generated in biological wastewater treatment plants [36].…”
Section: Introductionmentioning
confidence: 99%